INSULIN SECRETING ACTIVITY OF CAMELLIA SINENSIS ON ALLOXAN INDUCED DIABETES MELLITUS IN MALE WISTAR ALBINO RATS. - Andleeb Mumtaz Laghari1, Naveen Akmal2, Hafsa Usman Sheikh3, Shakeel Ahmed Sheikh4, Maria Jawed 5, Kulsoom Jawed6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Camellia Sinensis belongs to Theaceae family. It may be black tea, brown tea, green tea or oolong tea; all are derived from Camellia Sinensis. Camellia sinensis contains polyphenols, flavonoids, and catechins. Polyphenols possess antioxidant, anti-inflammatory and anti-microbial activity, and show probiotic properties. Growing interest has diverted the researchers to natural herbs for diabetes mellitus as complementary alternative therapy. OBJECTIVE: The present study is conducted to determine the insulin releasing effects of Camellia Sinensis in Alloxan induced diabetes mellitus in male Wistar Albino rat model. MATERIAL AND METHODS: The present experimental study was carried out at Department of Biochemistry LUMHS Jamshoro and animals were kept at Sindh agricultural university Tando Jam. Laboratory investigations were performed at the Diagnostic and Research Lab, LUMHS. Rats were purchased from the animal house of Agriculture University fulfilling the inclusion and exclusion criteria. Rats were housed in stainless steel cages with saw dust bedding. Animal housing and handling was in accordance to the NIH Guide (Care and Use of Laboratory Animals). A sample of n= 60 Albino Wistar rats were divided into negative control (A) and positive controls (B) and experimental group C (Diabetic rats given Alloxan 120 mg/kg body weight (bwt) i. p + C.sinensis 100 mg/kg bwt). Blood samples were collected from all 3 groups (A, B & C) through cardiac puncture after 4 weeks of experiment. Samples were taken in EDTA – containing tubes and plain tubes. Samples were centrifuged and sera collected for biochemical measuremen of serum insulin. Data was analyzed on SPSS version 22.0 (IBM, Incorp, USA). Variables were analyzed using one – way ANOVA (analysis of variance) and Fischer`s LSD post-Hoc testing. Level of statistical significance was at confidence interval 95% (p≤ 0.05). RESULTS: Fasting Insulin (FI) in control group A 10.49±1.06 µU/L compared to low levels in positive control group B noted as 3.44±0.81 µU/L. Camellia sinensis treated experimental group C shows 5.60±1.64 µU/L fasting insulin. F=176.2 value and P=0.0001 reveals Camellia sinensis therapy (30 days) increases the insulin secretion. CONCLUSION: In conclusion, the Camellia sinensis exerts significant insulin secretory potential in Alloxan induced male albino rat model. The findings are of clinical significance for treating an ever increasing diabetes health problem. However, further human studies are recommended with large sample size to validate the findings.